Ultramorphology and histology of the venom gland of workers of Apis mellifera (Hymenoptera, Apidae) before and after an electrical shock treatment - Magalhães de Abreu, Rusleyd Maria; Caetano, Flávio Henrique [UNESP]; Silva de Moraes, Regina Lúcia Morelli [UNESP]; Camargo-Mathias, Maria Izabel [UNESP] (My University, 2005)
This paper describes the ultramorphology and histology of the venom reservoir in 14-day old workers of Apis mellifera, immediately before and after the application of electrical shocks with the object of causing venom elimination and reservoir collapse. The external epithelial surface of the reservoir was differentiated according to its morphological aspects into posterior, median, and proximal or duct regions at the ventral surface and into anterior and posterior regions at the dorsal surface. While the epithelium of the proximal region forms a ventral infolding, a dorsal salience is formed at this region. These structures and the epithelial regions persist both in full and empty reservoirs. The reservoir appeared full and distended before the electrical shocks were applied and became empty and withered afterwards due to the elimination of the secretion, without any reductions in length. Nevertheless, some secretion was kept inside the lumen, thus suggesting a possible role for the reservoir in the modification of the secretion.
Keywords: Electric shock treatment; Histology; Honey bee; Ultrastructure; Venom gland; Apidae; Apis mellifera; Hymenoptera